4x+3+3x=7x+3

Simple and best practice solution for 4x+3+3x=7x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+3+3x=7x+3 equation:


Simplifying
4x + 3 + 3x = 7x + 3

Reorder the terms:
3 + 4x + 3x = 7x + 3

Combine like terms: 4x + 3x = 7x
3 + 7x = 7x + 3

Reorder the terms:
3 + 7x = 3 + 7x

Add '-3' to each side of the equation.
3 + -3 + 7x = 3 + -3 + 7x

Combine like terms: 3 + -3 = 0
0 + 7x = 3 + -3 + 7x
7x = 3 + -3 + 7x

Combine like terms: 3 + -3 = 0
7x = 0 + 7x
7x = 7x

Add '-7x' to each side of the equation.
7x + -7x = 7x + -7x

Combine like terms: 7x + -7x = 0
0 = 7x + -7x

Combine like terms: 7x + -7x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| X+X+27+3X-33=764 | | -11.6x=104.4 | | 3x^2+5x-1=7x+7 | | -3/7(m-9)=3+6m | | 13x-2(3x+4)=22 | | 2*0/1=4+y | | x/5=14/35 | | 13x-2(3x+4)=32 | | -(6y+1)-(-5Y-4)=-5 | | 6x-54=3x-12 | | x+0.2x=36 | | 13x-143=6x-10 | | n+6=6-6n | | F^2/4g^3/f^4/8g^4 | | 14s+32=2s | | 15x+x=13x-19 | | 10(x+6)=4(x+27) | | 5+5+5=250 | | 2(x-4)=32-6x | | 800=0.8Y-16r | | 3x-8=57-10x | | 11x+5=4x+54 | | 3+2s-2=9s+11-5s | | 5/2(-11,11) | | 3x+15/2x^2+15x+25 | | 1+7x=10x-22 | | 7+4x=54 | | .3(2x-5)=3 | | 2x-7=4/(2x-7) | | 21=17+z/2 | | x(2*2-5)=3 | | 6x/2=4 |

Equations solver categories